Securing “Functional” Legal Eternity in Italy: Parliamentary Procedures, Electoral Legislation and the Free Mandate for Members of Parliament - Fabio Pacini; Giuseppe Martinico; Giacomo Delledonne (Revista de Investigações Constitucionais, 2021)
This article addresses the subject of the free mandate for parliamentarians in Italy in relation to eternity clauses or inadmissible changes of the constitution, considering Italy’s constitution prevents amendments regarding some of its principles. This sort of counter-majoritarian devices protect constitutions from major changes and it gains importance due to the rise of new forms of populism. The article examines the relation between the electoral system and the free mandate for parliamentarians in Italy, recently changed by populist forces. Therefore the research outlines the context of Italian constitutionalism, and then addresses the role of parliaments and the “procedures” in this scenario, reaching the subject of the role of electoral legislation on the constitutional order, especially regarding the involvement of constitutional courts in electoral law. Finally, it discusses the free mandate for MPs, showing how complex constitutional principles are at stake, such as equality and representation. It concludes that electoral law should be interpreted and reviewed in the light of all the relevant constitutional principles and also should be protected from populist moves. The article uses a logical-deductive methodology with legislative and theoretical analysis of the subject.